A computational model of language learnability and language change - Clark, Robin; Roberts, Ian (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
This paper develops the idea that language change is guided by the restructuring of the target grammar during the child's language acquisition. The idea is formalized in terms of the generative model of Principles and Parameters. In this theoretical framework, acquisition is seen as a process of setting parametric values and linguistic change occurs when the population converges from a v value to at least one P parameter while adult grammar presents P and v. Although the basic idea is very compelling, there is an important unanswered question: how and why can the "adult" value of P be disregarded by the language-buying population? This article attempts to answer this question from Clark's (1990a, b, c) work on the application of genetic algorithms in parametric fixation and the analysis of parametric changes suffered by the French in the 19th century. XVI, proposed by Roberts (forthcoming).